Effect of foliar application of chemicals on quality and yield economics of garlic (Allium sativum) var. GG-4 (Current Horticulture, 2024)
An experiment was conducted to find out the effect of foliar application of chemicals on quality and yield economics of garlic (Allium sativum L.) var. GG-4 during rabi season of 2015-16 at Regional Horticultural Research Station, Navsari Agricultural University, Navsari. The experiment was laid out in a randomized block design with three replications and nine treatments. The quality parameters like TSS (%) and ascorbic acid (mg/100 g) were significantly influenced by foliar application of 100 ppm citric acid + 300 ppm thiourea (T8) with maximum value of 44.77% and 17.02 mg/100 g, respectively, whereas maximum storage days (179.33 days) were also observed in the same treatment. Moreover, sulphide content showed non-significant affect among different treatments. The maximum net return of ` 2,28,415 with a benefit: cost ratio (4.29) was obtained when plants were treated with 100 ppm citric acid + 300 ppm thiourea (T8).
Keywords: Chemicals; Foliar spray; Quality; yield economic; TSS; Ascorbic acid; Thiourea